1)
5х^2-7х+2=0
х=(7+/-())/2*5=(7+/-())/10=(7+/-3)/10
х=(7-3)/10=0,4
х=(7+3)/10=1
Ответ. х=0,4; х=1
2)
3)
5+х>3х-3(4х+5)
5+х>3х-12х-15
5+х>-9х-15
х+9х>-15-5
10х>-20
х>-2
Ответ. х>-2
4) Из первого уравнения найдем у:
у=1-2х
Подставим данное выражение во второе уравнение системы:
5х+2(1-2х)=0
5х+2-4х=0
х+2=0
х=-2
Ответ. х=-2
Ответ:
1. а) -100; б)98
2. а) -2; б) 5
3. а) 1; б) 8
4. а) -35 б) 0
p=4500м
f=5мин
h1=400м/мин
h2-?
Ш:f×(h1+h2)=p
5×(400+х)=4500
2000+5х=4500
5х=4500-2000
5х=2500
Х=2500÷5
Х=500
Ж:h2=500м/мин
Пошаговое объяснение: